Artificial intelligence and SMEs in developing economies - Olubiyi, Timilehin Olasoji, 1978-; Tambunan, Tulus, 1956- (Routledge, 2026)
"Artificial Intelligence and Small Businesses in Emerging Economies explores the emergence and application of Artificial Intelligence in developing economies. This is in response to the shift in Artificial Intelligence research towards the achievement of Sustainable Development Goals (SDGs), as well as the environmental problems and methods to solve them. Written by experts from around the globe from developing countries, the book contains a balance of theoretical and empirical chapters that explore Artificial Intelligence in the context of business. It focuses especially on integrating industry 5.0 where Artificial Intelligence plays a major role. The chapters include knowledge and applications for small businesses, ranging from disruptive Artificial Intelligence technologies to determinants of Artificial Intelligence adoption in SMEs from major developing economies such as Africa, Latin America and Asia. In the latter chapters, the book discusses the application of Artificial Intelligence, such as how to leverage it for sustainable and responsible small businesses, and the importance of appreciating in a business environment. This book is the first substantial study on Artificial Intelligence and the future of sustainable small businesses in emerging economies. It is a useful resource for academics and university students with interest in Artificial Intelligence and sustainable small businesses, specifically small business development. It is also a valuable read for policy makers and SME stakeholders"-- Provided by publisher.
Keywords: Small business -- Developing countries.; Sustainable development -- Developing countries.; Artificial intelligence -- Developing countries.; elektronické knihy; electronic books